The Others and Their Stories: Byzantines, Franks, Lombards and Saracens in Ninth-century Neapolitan Narrative Texts. (April 2016) - Berto, Luigi Andrea
The ninth century was a fundamental period for the history of Naples. Newly untethered from Constantinople and trying to forge a stable state, the Campanian city faced a complex political landscape in Southern Italy. The Frankish conquest of the Lombard kingdom and the weakening of the Byzantine Empire, which allowed the Saracens to seize Sicily, reshaped the South into a region dominated by several competing protagonists. Naples resisted conquest at the hands of the neighbouring Lombards of Benevento while simultaneously maintaining peaceful relationships with the two empires and the Saracens. The goal of this article is to examine how Neapolitan authors portrayed Byzantines, Franks, Lombards and Saracens, and what they knew about them. In particular, it will focus on the Gesta Episcoporum Neapolitanorum ( Deeds of the Neapolitan Bishops ) by John the Deacon—the main Neapolitan source for that epoch.